2010 IEEE International Symposium on Hardware-Oriented Security and Trust (HOST) 2010
DOI: 10.1109/hst.2010.5513111
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping platform for performance evaluation of SHA-3 candidates

Abstract: The objective of the SHA-3 NIST competition is to select, from multiple competing candidates, a standard algorithm for cryptographic hashing. The selected winner must have adequate cryptographic properties and good implementation characteristics over a wide range of target platforms, including both software and hardware. Performance evaluation in hardware is particularly challenging because of the large design space, wide range of target technologies, and multitude of optimization criteria. We describe the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…There exist several Keccak implementations where most of them have been designed for FPGAs. Highspeed implementations have been reported by J. Strömbergson [39], B. Baldwin et al [3], E. Homsirikamol et al [22], K. Kobayashi et al [31], F. Gürkaynak et al [20], and K. Gaj et al [16,17]. Low-area FPGA designs have been presented by S. Kerckhof et al [29], J.-P. Kaps et al [26], and B. Jungk and J. Apfelbeck [25].…”
Section: Hash Functions For Rfidmentioning
confidence: 99%
“…There exist several Keccak implementations where most of them have been designed for FPGAs. Highspeed implementations have been reported by J. Strömbergson [39], B. Baldwin et al [3], E. Homsirikamol et al [22], K. Kobayashi et al [31], F. Gürkaynak et al [20], and K. Gaj et al [16,17]. Low-area FPGA designs have been presented by S. Kerckhof et al [29], J.-P. Kaps et al [26], and B. Jungk and J. Apfelbeck [25].…”
Section: Hash Functions For Rfidmentioning
confidence: 99%
“…Since then, several comprehensive studies in SHA-3 ASIC implementations have been reported [6]- [13]. Guo et al [6] used a consistent and systematic approach to move the SHA-3 hardware benchmark process from the FPGA prototyping by Kobayashi et al [14] to ASIC implementations based 130nm CMOS standard cell technology. Tillich et al [8] presented the first ASIC post-synthesis results using 180nm CMOS standard cell technology with high throughput as the optimization goal and further provided post-layout results [7].…”
Section: Related Workmentioning
confidence: 99%
“…Regarding hardware implementations of the JH algorithm, to the best of authors' knowledge, there are no previously published works dealing with the JH algorithm itself. However, there are several ones performing comparative analyses among either the round-two candidates (Baldwin et al, 2010); (Henzen et al, 2010); (Tillich et al, 2009); (Matsuo et al, 2010); (Homsirikamol et al, 2010); (Gaj et al, 2010); (Guo et al, 2010a); (Guo et al, 2010b); (Kobayashi et al, 2010), or the round-3 candidates (Jungk et al, 2011); (Kerckhof et al, 2011); (Guo et al, 2011); (Guo et al, 2012); (Jungk, 2011); (Homsirikamol et al, 2011); (Tillich et al, 2010); (Provelengios et al, 2011). The above studies include both FPGA and ASIC CMOS implementations.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, FPGA implementations and results are reported in 10 papers (Baldwin et al, 2010); (Matsuo et al, 2010); (Homsirikamol et al, 2010); (Gaj et al, 2010); (Guo et al, 2010a); (Kobayashi et al, 2010); (Jungk et al, 2011); (Jungk, 2011); Homsirikamol et al, 2011;Provelengios et al, 2011).…”
Section: Related Workmentioning
confidence: 99%